Effects of slotted structures on the nonlinear characteristics of natural convection in a cylinder with an internal concentric slotted annulus. (1st September 2016) - Shen, Chunyun; Yang, Mo; Zhang, Yuwen; Li, Zheng
ABSTRACT: Natural convection in a cylinder with an internally slotted annulus was solved by SIMPLE algorithm, and the effects of different slotted structures on the nonlinear characteristics of natural convection were investigated. The results show that the equivalent thermal conductivity K eq increases with Rayleigh number, and reaches the maximum in the vertical orientation. Nonlinear results were obtained by simulating the fluid flow at different conditions. With increasing Rayleigh number, heat transfer is intensified and the state of heat transfer changes from steady to unsteady. We investigated the effects of different slotted structures on natural convection and analyzed the corresponding nonlinear characteristics.